Penerapan Kesehatan Kerja untuk Peningkatan Produktivitas UMKM di Kota Bandung - Harun Heri Trismiyanto; Lita Wulantika (Pusat Riset dan Inovasi Nasional, 2025)
The productivity of micro-enterprises, particularly in the culinary sector, plays a critical role in supporting local economic growth. However, productivity is often influenced by the welfare and occupational health conditions of business actors, which remain significant issues. This study aims to analyze the effect of health on the productivity of culinary micro-enterprises in Bandung City. A quantitative approach using a simple linear regression method was employed to evaluate the relationship between health and productivity. The sample consisted of 80 entrepreneurs, selected using purposive sampling with criteria that the businesses had been operating for at least two years and employed permanent workers. Data were collected through a Likert-scale-based questionnaire and analyzed using SPSS version 25, applying Model Summary, ANOVA, and regression coefficient tests. The results indicate that health has a positive effect on productivity, yet the relationship is weak and statistically insignificant. These findings suggest that while occupational health is a factor in productivity, it cannot fully explain the variations in productivity levels observed across the sample. Consequently, other variables, such as innovation, managerial strategies, and technological support, must be considered to achieve a more comprehensive understanding of what drives productivity in culinary micro-enterprises. The implications of these findings highlight the necessity for more comprehensive policies and programs to improve the productivity of micro, small, and medium enterprises (MSMEs). By integrating health considerations with other supportive factors such as innovation and technology, MSMEs can be better positioned for sustainable growth and competitiveness in the market